Additive‐like amounts of HDPE prevent creep of molten LDPE: Phase‐behavior and thermo‐mechanical properties of a melt‐miscible blend. Issue 2 (26th October 2016) - Andersson, Mattias G.; Hynynen, Jonna; Andersson, Mats R.; Hagstrand, Per‐Ola; Gkourmpis, Thomas; Müller, Christian
ABSTRACT: Low‐density polyethylene (LDPE) is the preferred type of polyolefin for many medical and electrical applications because of its superior purity and cleanliness. However, the inferior thermo‐mechanical properties as compared to, for example, high‐density polyethylene (HDPE), which arise because of the lower melting temperature of LDPE, constitute a significant drawback. Here, we demonstrate that the addition of minute amounts of HDPE to a LDPE resin considerably improves the mechanical integrity above the melting temperature of LDPE. A combination of dynamic mechanical analysis and creep experiments reveals that the addition of as little as 1 to 2 wt% HDPE leads to complete form stability above the melting temperature of LDPE. The investigated LDPE/HDPE blend is found to be miscible in the melt, which facilitates the formation of a solid‐state microstructure that features a fine distribution of HDPE‐rich lamellae. The absence of creep above the melting temperature of LDPE is rationalized with the presence of tie chains and trapped entanglements that connect the few remaining crystallites. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part B: Polym. Phys.2017, 55, 146–156 Abstract : The phase behavior of a melt‐miscible blend of low‐density polyethylene (LDPE) and high‐density polyethylene (HDPE) is investigated. Complete miscibility is found in the melt for the whole composition range. Addition of as little as 1 wt% HDPE is found to introduce additional tie chains that prevent creep above the melting temperature of LDPE.